1970
DOI: 10.1021/ja00718a021
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity in the debromination of the stilbene dibromides with stannous chloride in dimethylformamide

Abstract: The debromination of meso-or ¿/-stilbene dibromide by stannous chloride in dimethylformamide is a second-order reaction. The rate data at 59.4°are as follows: for meso, k = 3.73 X 10-4 M-1 sec-1, AH* = 15.5 kcal/mol, 5* = -28 eu; for dl, k = 3.36 X 10-s M-1 sec-1, AH* = 19.3 kcal/mol, AS* = -21 eu.The meso gives only zra/zs-stilbene, while the dl gives ca. 95% trans-and 5% c/s-stilbene over the range 60-100°. A concerted E2 process seems appropriate for meso, but this is difficult to verify. The formation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…In a preliminary study of 1,2-debromination reactions, we found the stereospecificity of the well-known anti elimination product to be comparable to that obtained from the best of the previously described procedures (17). For example, while many reducing reagents give stereospecific trans-alkene formation on debromination of meso-1,2-dibromides, in the difficult cis-alkene cases, such as the formation of cis-stilbene from (+)-I ,2-dibromo-l,2-diphenylethane, the resulting stereospecificity is often poor or nonexistent (18,19). However, use of the PPN+-Cr(CO),NO-metallate (20) at -78°C gave a 19: 1 cisltransstilbene mixture.…”
Section: Introductionmentioning
confidence: 73%
“…In a preliminary study of 1,2-debromination reactions, we found the stereospecificity of the well-known anti elimination product to be comparable to that obtained from the best of the previously described procedures (17). For example, while many reducing reagents give stereospecific trans-alkene formation on debromination of meso-1,2-dibromides, in the difficult cis-alkene cases, such as the formation of cis-stilbene from (+)-I ,2-dibromo-l,2-diphenylethane, the resulting stereospecificity is often poor or nonexistent (18,19). However, use of the PPN+-Cr(CO),NO-metallate (20) at -78°C gave a 19: 1 cisltransstilbene mixture.…”
Section: Introductionmentioning
confidence: 73%
“…be initiated by nucleophilic attack by the trimethylstannyl anion on the bromine, as represented in eq 11. The in- (11) termediate carbanion 8 would undergo inversion rapidly relative to loss of methoxide ion and to reaction with trimethylbromostannane, resulting in nonspecific overall reactions. A series of experiments designed to test this mechanism by trapping any carbanion formed with tertbutyl alcohol was carried out with the results depicted in Figure 4.…”
Section: Discussionmentioning
confidence: 99%